Perception and Problem of English Pre-service Teachers in Applying Merdeka Belajar Curriculum During Teaching Practice - Achadiyah, Rachmawati; Azmi, Muhammad Ulul (Journal of English Education Program, 2024)
Curriculum is updated according to the era's demands which aims at actualizing qualified human resources. The great concept of the curriculum will be superfluous without the teachers"™ role. The objective of this research is to examine English preservice teachers"™ perceptions and problems they encounter in understanding and implementing the new curriculum during their teaching practice. Ten English preservice teachers who completed their teaching practice took part in this research. They were assigned to schools that implement the Merdeka Belajar curriculum. Since the data was gathered and analyzed in two ways, this research is a mixed-method study. The findings of the study revealed that English preservice teachers have a negative perception of understanding and implementing the Merdeka Belajar curriculum in their teaching practice, incapability in designing flow of learning objectives and teaching modules, incapability to conduct differential learning, lack of knowledge on how to integrate Profil Pelajar Pancasila into teaching-learning process contributes to the negative perception of English Pre-Service Teacher. Additionally, the problem was made worse because the university did not properly prepare English pre-service teachers for the latest curriculum.